Ceropegia setuligera, a new species of Apocynaceae from Xizang, China - Liao, Wei-Hua; Qu, Ke; Liu, Si-Qi; Zhang, Tong; Xu, Bo; Li, Meng (Phytotaxa, 2026)
Ceropegia setuligera, a new species from Mêdog, Xizang, China, is described and illustrated. This new species is morphologically similar to C. pubescens and C. hookeri, but can be distinguished by its indumentum, swollen internodes of lateral branches, the size of the corolla, and the shapes of the corolla lobes and staminal corona lobes. Phylogenetic analyses based on nuclear ribosomal DNA region (nrITS) and four plastid markers (trnL-trnF, trnS-trnG, psbA-trnH and rps16) support the placement of C. setuligera within C. sect. Chionopegia, and recovered it as sister to C. pubescens. A comparative table and illustrations of the morphologically similar species are provided.